Pengaruh Pemberian Kode Warna Wilayah Pada Folder Terhadap Ketepatan Penyimpanan Berkas Rekam Medis Di Puskesmas Wadaslintang 1 - Deni Gunawan (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
A Medical records are files containing notes and documents regarding the patient's identity, examination, treatment, actions and other services that have been provided to patients. So that a medical file is strictly protected so that it is not damaged or lost.Based on observations, it was found that there were several files of medical records that were interchanged or not in the normal filling rack. Medical record files can be exchanged due to the large number of regional shelf columns so that alternatives and innovations are needed to increase the accuracy of returning and retrieving medical record files correctly.Troubleshooting efforts are being made, namely by providing a regional color code in the medical record file folder so that errors in taking and returning medical record files can be minimized.Based on the results of observations made by the author, it was found that there was an effect before and after color coding the region in the medical record file folder.